Evidence for PII with NAGK interaction that regulates Arg synthesis in the microalga Myrmecia incisa in response to nitrogen starvation. Issue 1 (December 2017) - Li, Yan; Liu, Wei; Sun, Li-Ping; Zhou, Zhi-Gang
Abstract To understand why most eukaryotic microalgae accumulate lipids during nitrogen starvation stress, a gene, MiglnB, encoding PII, a signal transduction protein, was cloned from the arachidonic acid-rich microalgaMyrmecia incisa Reisigl. Similarly to its homologues, MiPII contains three conserved T-, B-, and C-loops. In the presence of abundant Mg2+, ATP, and Gln, MiPII upregulates Arg biosynthesis by interacting with the rate-limiting enzyme, MiNAGK, as evidenced by yeast two-hybrid, co-immunoprecipitation assays, and kinetics analysis of enzyme-catalyzed reactions. However, this interaction of MiPII with MiNAGK is reversed by addition of 2-oxoglutarate (2-OG). Moreover, this interaction is present in the chloroplasts ofM .incisa, as illustrated cytologically by both immunoelectron microscopy and agroinfiltration ofNicotiana benthamiana leaves to determine the subcellular localization of MiPII with MiNAGK. During the process of nitrogen starvation, soluble Arg levels inM .incisa are modulated by a change in MiNAGK enzymatic activity, both of which are significantly correlated (r  = 0.854). A model for the manipulation of Arg biosynthesis via MiPII inM .incisa chloroplasts in response to nitrogen starvation is proposed. The ATP and 2-OG saved from Arg biosynthesis is thus suggested to facilitate the accumulation of fatty acids and triacylglycerol inM .incisa during exposure to nitrogen starvation.